2012
DOI: 10.5120/8549-2109
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Recognition of Elderly Daily Activity using Fuzzy Logic through Fusion of Motion and Location Data

Abstract: One of the major problems that may encounter old people at home is falling. Approximately, one of three adults of the age of 65 or older falls every year. The World Health Organization reports that injuries due to falls are the third most common cause of chronic disability. In this paper, we proposed an approach to indoor human daily activity recognition, which combines motion and location data by using a webcam system, with a particular interest to the problem of fall detection. The proposed system identifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…More specifically, in the field of activity recognition with focus to fall detection, many recent studies can be found in the literature [1,2,6,3]. Some studies use microphones to detect falls, while others use information obtained by cameras that track the movement and the trajectory of humans in assisted environments, where long and/or unusual inactivity can be interpreted as a fall.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in the field of activity recognition with focus to fall detection, many recent studies can be found in the literature [1,2,6,3]. Some studies use microphones to detect falls, while others use information obtained by cameras that track the movement and the trajectory of humans in assisted environments, where long and/or unusual inactivity can be interpreted as a fall.…”
Section: Introductionmentioning
confidence: 99%
“…Πολλά ολοκληρωμένα συστήματα έχουν παρουσιαστεί στη βιβλιογραφία [33,34,77,89], που σκοπό έχουν το εντοπισμό ενός επείγοντος περιστατικού και στη συνέχεια ενημέρωση ενός οικείου προσώπου για βοήθεια. Μέθοδοι που μπορούν να εντοπίσουν την πτώση ενός ανθρώπου με την χρήση κάμερας, όπως παρουσιάσαμε στα Κεφάλαια 3 και 4, δίνουν την ευκολία της διακριτικής επιτήρησης, χωρίς να επεμβαίνουν στον ίδιο τον άνθρωπο αλλάζοντάς του τον καθημερινό τρόπο ζωής του.…”
Section: εισαγωγήunclassified